The role of gas chromatography in halal food authentication: Principles, applications, and challenges – A systematic literature review - Nisa Irdina Rahman; Indah Kusumawati; Sami Nazzal (Journal of Halal Science and Research, 2026)
The global demand for halal products continues to rise, driving the need for accurate scientific analytical methods to ensure authenticity and compliance with halal standards. This systematic review aims to examine the application of gas chromatography, including its role, applications, and challenges, in halal food authentication. However, existing studies are mostly fragmented and focus on specific products or individual analytical approaches, and a comprehensive evaluation of GC applications, methodological challenges, and future directions in halal authentication remains limited. The research method used was a systematic literature review with the PRISMA approach of scientific publications from 2015 – 2025 obtained from five major databases: ScienceDirect, PubMed, Semantic Scholar, OpenAlex, and Google Scholar. Of the 1,121 articles identified, 33 met the inclusion criteria and were analyzed in depth. The analysis revealed that GC techniques, particularly GC–MS, GC–FID, HS-SPME–GC–MS, and GC–FAMEs, have been extensively applied for the authentication of meat, fat, gelatin, and fermented beverages through the identification of marker compounds such as aldehydes, ketones, alcohols, and fatty acid methyl esters (FAMEs). These techniques proved effective in differentiating halal and non-halal meat species, detecting pork fat adulteration, and verifying ethanol content in beverages. The conclusion shows that GC has high sensitivity and selectivity in halal authentication, but still faces limitations such as matrix complexity, operational costs, and the need for expert personnel. Research gaps identified include the lack of standardized GC protocols, limited studies on complex processed products, and minimal integration with chemometric analysis, necessitating the development of more standardized and applicable methods. Keywords: Chemometrics, Gas chromatography, Halal authentication, Lipidomics, Volatilomics.